The Development of Disaster Mitigation Curriculum to Improve Disaster Response Capabilities At The Elementary School In Indonesia - Wahyu Pratama Putra; Dian Ahmad Sasmito; Rachima Dianovitasari Divian Kass (EDUVELOP, 2021)
Abstract: Disasters threaten the safety of vulnerable groups such the eldery, children and women. Based on the case of natural disasters that occurred in Indonesia, the need for a pragmatic strategy in forming the Indonesian people are aware of the dangers of natural disasters. One strategic step that taken is through the education sector. This research aims to create a disaster mitigation curriculum that has been formulated to produce disaster responsive learners. This research uses R&D (research and development method) by Borg and Gall (2003), in the stages of research and information, planning and initial product development. While for curriculum development used the Tyler model with the infusion method and block method. Data collection techniques used namely interviews, observation, and documentation. The findings of this research are based curriculum products to the stages of disaster mitigation include, 1) the concept of disaster mitigation curriculum, 2) The concept of the learning process (Intrakurikuler), 3) The concept of training process (Extracurricular, and 4) The concept of the assessment process (Evaluation). These results indicate curriculum products are made to increase disaster response capabilities of students through intracurricular and extracurricular activities as well as minimizing the impact of the disaster victims and improve disaster response capabilities for students in Indonesia. Keywords: Curriculum, Disaster Mitigation, Tyler's Model.